Awe and respect in the Psalms - Waaijman, K. (Acta Theologica, 2008)
This essay discusses the motif of awe in the Psalms in terms of Buber’s outline of mystical awe. In a first section, awe as the beginning of wisdom is analysed, followed by a discussion of the experience of Be-er’s1 (Yahweh’s) goodness. In a third section, attention is given to awe as the quiet waiting on Be-er, followed, in a final part, by an analysis of love as the result of awe.